Evidence of soluble microbial products accelerating chloramine decay in nitrifying bulk water samples - Bal Krishna, K; Sathasivan, Arumugam; Sarker, Dipok (IWA Publishing, 2012)
The discovery of a microbially derived soluble product that accelerates chloramine decay is described. Nitrifying bacteria are believed to be wholly responsible for rapid chloramine loss in drinking water systems. However, a recent investigation showed that an unidentified soluble agent significantly accelerated chloramine decay. The agent was suspected to be either natural organic matter (NOM) or soluble microbial products (SMPs). A laboratory scale reactor was fed chloraminated reverse osmosis (RO) treated water to eliminate the interference from NOM. Once nitrification had set in, experiments were conducted on the reactor and feed waters to determine the identity of the component. The study showed the presence of SMPs released by microbes in severely nitrified waters. Further experiments proved that the SMPs significantly accelerated chloramine decay, probably through catalytic reaction. Moreover, application of common protein denaturing techniques stopped the reaction implying that the compound responsible was likely to be a protein. This significant finding will pave the way for better control of chloramine in the distribution systems.